The Firefox Kid. - Kushner, D. (IEEE spectrum)
Blake Ross, one of the developers of Firefox which is one of the biggest open-source success stories is developing again a new project named Parakey. It is a Web operating system that can do everything an OS can do. It makes it really easy to store your stuff and share it with the world. There are differences between the two projects, however. Although Ross plans to incorporate the talents and passions of the free-software community, he's building Parakey around a for-profit business model